Taxpayer Awareness, Tax Services, Taxpayer Counseling, Tax Audit, Tax Rates And Tax Sanctions On The Compliance Of Individual Business Public People (case study at Regional Office of DGT East Java II) - Muhammad Primbang Apriliyanto; Hwihanus Hwihanus (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to analyze taxpayer awareness, tax services, taxpayer counseling, tax audits, tax rates and tax sanctions on individual entrepreneur taxpayer compliance at the Regional Office of DJP East Java II. The population in this study are all individual business taxpayers who are registered at the Tax Service Office (KPP) in the East Java II Regional Office of DJP. With a research sample of 3 businessman OP taxpayers with descriptive qualitative methodological techniques. Data collection was carried out through interviews, observation and documentation. The results of this study prove that partially taxpayer awareness, tax services, taxpayer counseling, tax audits, tax rates and tax sanctions have a positive and significant effect on individual entrepreneur taxpayer compliance at KPP-KPP in the Regional Office of DJP East Java II. This means that the increasing awareness of taxpayers, good tax services, counseling of taxpayers, tax audits, tax rates and tax sanctions, the taxpayer compliance will be better (increased).